El Acuerdo Fiscal entre España y el Reino Unido en relación con Gibraltar - Alejandro Garcia Heredia (Cuadernos de Gibraltar, 2021)
This paper analyzes the International Agreement on taxation and the protection of financial interests between Spain and the United Kingdom regarding Gibraltar. The paper deals with the two fundamental issues of this Agreement: the tax residency rules and the system of administrative cooperation in tax matters.